2013
DOI: 10.1371/journal.pone.0074168
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Ferritin Levels and Risk of the Metabolic Syndrome in Chinese Adults: A Population Study

Abstract: Ferritin is a ubiquitous intracellular protein that can store and release iron and act as a buffer against iron deficiency and iron overload. Ferritin is widely used as a clinical biomarker to evaluate iron status. Increased serum ferritin concentrations have been reported to be associated with metabolic syndrome (MetS) features. However, serum ferritin concentrations differ significantly according to sex and ethnicity, and the data concerning the relationship between serum ferritin concentrations and MetS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 36 publications
7
37
0
1
Order By: Relevance
“…The results of our study showed that serum ferritin level of the MetS group was higher than that of the non-MetS group (p<0.001) in the each of the gender-based groups. These results are consistent with previous studies [14,29] that did find significant differences in serum ferritin related to MetS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study showed that serum ferritin level of the MetS group was higher than that of the non-MetS group (p<0.001) in the each of the gender-based groups. These results are consistent with previous studies [14,29] that did find significant differences in serum ferritin related to MetS.…”
Section: Discussionsupporting
confidence: 93%
“…Among previous studies on serum ferritin concentration and MetS, Li and colleagues reported that serum ferritin levels were positively associated with MetS in both Chinese men and women [29]. Moreover, Vari and colleagues reported that serum ferritin levels were positively associated with MetS in French men and premenopausal women and postmenopausal women [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some papers have reported an association between serum ferritin levels and risk for MetS; high-normal ferritin concentrations are associated with central adiposity (19), hypertension (20), elevated fasting insulin and blood glucose (21), dyslipidemia (22) and MetS (23). The relationships between ferritin and TG and between ferritin and FPG observed our study completely concurred with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Existe evidencia de que concentraciones séricas elevadas de ferritina se asocian con mayor riesgo de desarrollo de diabetes y sus complicaciones (28) , resistencia a la insulina (29) , síndrome metabólico (30) e hipertensión (31) . Cuando la exposición a la inflamación es alta, se recomiendan el uso como biomarcadores la concentración de receptor de transferrina soluble (RTfs) (ver abajo) o la relación de RTfs:ferritina ya que serían menos afectados por el proceso inflamatorio (27) .…”
Section: Ferritinaunclassified